1996
DOI: 10.1172/jci118435
|View full text |Cite
|
Sign up to set email alerts
|

Hyperproinsulinemia is associated with increased beta cell demand after hemipancreatectomy in humans.

Abstract: The cause of disproportionate hyperproinsulinemia in patients with type II diabetes is controversial. To examine whether increased ␤ cell demand might contribute, we measured proinsulin and insulin concentrations in clinically healthy humans who had undergone hemipancreatectomy for the purpose of organ donation, a procedure previously demonstrated to increase ␤ cell demand and diminish insulin secretory reserve capacity. Subjects were studied at least 1 yr after hemipancreatectomy. Seven donors were followed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 35 publications
(33 reference statements)
7
55
2
Order By: Relevance
“…As reported for pancreas transplantation [18], basal fasting glucose concentrations after overnight withdrawal of insulin were predictors of outcome, being markedly increased one month after transplantation only in recipients who did not become insulin independent. Also fasting proinsulin values after overnight withdrawal of insulin were found to be increased in our patients with a poor functioning graft, in line with that reported in patients with newly diagnosed Type II diabetes [19], in hemipancreatectomized patients [20] and in a case report of islet transplantation in Type I diabetic patient [21]. In view of these data, the transplantation of further islets should be considered already 1 month after transplantation in patients who have higher fasting blood glycaemia and proinsulinemia or both.…”
Section: Discussionsupporting
confidence: 91%
“…As reported for pancreas transplantation [18], basal fasting glucose concentrations after overnight withdrawal of insulin were predictors of outcome, being markedly increased one month after transplantation only in recipients who did not become insulin independent. Also fasting proinsulin values after overnight withdrawal of insulin were found to be increased in our patients with a poor functioning graft, in line with that reported in patients with newly diagnosed Type II diabetes [19], in hemipancreatectomized patients [20] and in a case report of islet transplantation in Type I diabetic patient [21]. In view of these data, the transplantation of further islets should be considered already 1 month after transplantation in patients who have higher fasting blood glycaemia and proinsulinemia or both.…”
Section: Discussionsupporting
confidence: 91%
“…In each case, a very marked decrease in insulin content and degranulation was observed and elevated proinsulin secretion was seen to be the consequence of the relative immaturity of the granule population. In humans, a decrease in -cell mass produced by hemipancreatectomy (Seaquist et al 1996) induces a 5-to 6-fold increase in circulating proinsulin without major excursions in plasma glucose. Likewise low-dose streptozotocin in a non-human primate can cause hyperproinsulinemia without hyperglycemia (Kahn et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of hyperproinsulinemia in diabetes has variously been attributed to deficiency in -cell prohormone convertase (PC) activity (Rhodes & Alarcon 1994), changes in the intragranular processing environment (pH and Ca changes) or asynchrony between stimulation of secretion and biosynthesis (Bollheimer et al 1998). Incomplete processing could equally arise from increased secretory granule turnover as a direct consequence of the increased demands imposed by peripheral insulin resistance or decreased functional -cell mass (Alarcon et al 1995, Gadot et al 1995, Seaquist et al 1996, Laedtke et al 2000. Another possibility could be regulation of the prohormone endopeptidases PC1 and PC2 by endogenous chaperonins or protease inhibitors in the pancreatic -cell such as PC-derived propeptides (Fugere et al 2002) or PC inhibitors 7B2 and ProSAAS (Benjannet et al 1995, Feng et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies suggest that, either an inherent beta-cell defect [5,6] or an increased secretory demand [7,8] is responsible for relative hyperproinsulinaemia. The results of our study suggest that an impaired beta-cell function is primaryly responsible for relative hyperproinsulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are often interpreted as early indicators of an impaired beta-cell function but the mechanisms underlying the increase in proinsulin have still not been established. The results of some studies among patients with Type II diabetes have suggested that an inherent beta-cell defect is responsible for raised proinsulin [5,6], whereas studies with rats [7] and hemipancreatectomised patients [8] have suggested that an increased secretory demand on the beta-cells is responsible. In Type II diabetes, hyperglycaemia per se could contribute to the beta-cell defect.…”
mentioning
confidence: 99%